Microwave-assisted synthesis and characterization of chitosan aerogels doped with Au-NPs for skin regeneration. (February 2019) - Piątkowski, Marek; Radwan-Pragłowska, Julia; Janus, Łukasz; Bogdał, Dariusz; Matysek, Dalibor; Cablik, Vladimir
Abstract: Tissue engineering provides solutions for patients awaiting for transplantation. Tissue engineering solutions help doctors to deliver tissue equivalent to damaged tissue. Such treatment method requires advanced biomaterials which would not only enable cells proliferation but also help to maintain their viability. The aim of the present work was to develop new chitosan-based biomaterial with enhanced properties applicable in extend burn wounds healing. Chitosan scaffolds doped with Au nanoparticles were obtained under microwave-assisted conditions using only biocompatible and eco-friendly reagements. Ready materials were investigated inter alia over their chemical structure, morphology, biodegradability, antimicrobial activity and cytotoxicity. Obtained results show that proposed biomaterials are antibacterial and bioactive thus may be successfully applied in regenerative medicine. Highlights: Microwave-assisted synthesis method of biodegradable chitosan aerogels doped with Au NPs has been developed. Obtained polymeric scaffolds were investigated over their physicochemical properties. Chitosan aerogels had superior antibacterial properties. Biomaterials were non cytotoxic and had positive effect on proliferation activity of L929 mouse fibroblasts.